Evaluation of the Duration of Action and Comparative Effectiveness of Lisdexamfetamine Dimesylate and Behavioral Treatment in Youth With ADHD in a Quasi-Naturalistic Setting. (July 2015) - Manos, Michael J.; Caserta, Donald A.; Short, Elizabeth J.; Raleigh, Kristina L.; Giuliano, Kimberly C.; Pucci, Nicole C.; Frazier, Thomas W.
Objective: This study compared the relative effects of three treatment conditions: long-acting stimulant medication (MED), behavior modification, and medication/behavioral treatments combined (COM) in children with ADHD.Method: A total of 25 children, aged 6 to 12 years, received the three treatment conditions during a 7-week Summer Treatment Program in an alternating treatments design. Counselors completed behavioral ratings from 0.5 to 12.5 hr post dose, and parents completed nighttime ratings.Results: Ratings for SKAMP (Swanson, Kotkin, Agler, M-Flynn, and Pelham) and for following instructions indicated COM and MED improved symptoms over BEH treatment beginning 3 hr post dose ( p = .008), with ratings maintained 12.5 hr post dose ( p = .001 and .006). Results for frustration tolerance indicated significant improvement in all three conditions until 9 hr post dose.Conclusion: MED and COM separated from BEH at 3 hr post dose, and sustained benefit was observed across the day for two of three measures. BEH appears to have an additive effect, extending the duration of frustration tolerance.